The Increasing of Students’ English Speaking by Using Communicative Language Teaching (CLT) through Online Learning in Pandemic Covid-19 - Harahap, Nurul Husnah; Ramadani, Ramadani; Sanusi, Asri; Sinaga, Dwi Pebrina; Tampubolon, Marlina (Budapest International Research and Critics University, 2021)
This study dealt students’ English speaking by using Communicative Language Teaching (CLT) through Online Learning in Pandemic Covid-19. It is used qualitative research design. It was conducted descriptively. The purpose of this study was to know how the increasing of students’ English speaking by using Communicative Language Teaching (CLT) through Online Learning in Pandemic Covid-19. There were 30 students of AMIK Medicom Medan as sample in this study. There were two instrument that conducted in this study, they were observation and interview. The data were analyzed by Miles, Huberman and Saldana (2014) analysis. The result of this study was Communicative Language Teaching (CLT) had good role on teaching learning process. The students’ speaking increased significantly. The students talked more in this learning method. Then, the students felt happy and comfortable in teaching learning process. It can be proved by result of interview. CLT was able to make the students self confidence in practicing their speaking in front of crowded people and be good public speaking.